Ligand-Binding Sites in Vanilloid-Subtype TRP Channels - Yelshanskaya, Maria V.; Sobolevsky, Alexander I. (Frontiers in Pharmacology, 2022)
Vanilloid-subfamily TRP channels TRPV1-6 play important roles in various physiological processes and are implicated in numerous human diseases. Advances in structural biology, particularly the “resolution revolution” in cryo-EM, have led to breakthroughs in molecular characterization of TRPV channels. Structures with continuously improving resolution uncover atomic details of TRPV channel interactions with small molecules and protein-binding partners. Here, we provide a classification of structurally characterized binding sites in TRPV channels and discuss the progress that has been made by structural biology combined with mutagenesis, functional recordings, and molecular dynamics simulations toward understanding of the molecular mechanisms of ligand action. Given the similarity in structural architecture of TRP channels, 16 unique sites identified in TRPV channels may be shared between TRP channel subfamilies, although the chemical identity of a particular ligand will likely depend on the local amino-acid composition. The characterized binding sites and molecular mechanisms of ligand action create a diversity of druggable targets to aid in the design of new molecules for tuning TRP channel function in disease conditions.